PELATIHAN DAN PROMOSI BORDIR TAS TRADISIONAL BUDAYA ACEH BAGI MAHASISWA INTERNASIONAL UNIVERSITY NAGOYA GAKUIN JEPANG - Sri Wahyuni; Fauzi Fauzi; Muhammad Saleh; Hakim Muttaqim; Muhammad Rasyidin (LPPM Universitas Al Muslim, 2024)
Mom N Me is an MSME located in Lhok Mambang Village, Gandapura District, Bireuen Regency, Aceh Province, which is engaged in sewing and producing Acehnese embroidered bag crafts, as well as providing sewing training for the local community. The problem faced by MSME Mom N Me so far is that it only provides sewing training to local communities and has not yet provided sewing training on a district, provincial, national or international scale. Participants in this community service activity were 10 international students from Nagoya Gakuin University and 15 students from Al-Muslim University. Implementation of activities used observation, discussion and direct practice methods in the Mom N Me MSME learning room. Based on the results of the activity, it can be seen that this activity had a positive impact, both on knowledge and increasing participants' skills. In fact, it can be seen that participants completely participated in the training which was carried out face to face and there was interaction between the participants and the tutor (resource person). Apart from that, there was an increase in participants' knowledge, both Japanese students and Al-Muslim University students, about sewing, especially sewing Acehnese embroidered bags. This activity also has a positive impact on partners and participants, namely partners can promote local products to the international community, and Japanese students can learn local culture and Indonesian easily through direct interaction with the local community.